Efektivitas Pendekatan Saintifik Metode 5M dalam Peningkatan Kemampuan Menulis Karya Ilmiah - Ganes Tegar Derana; Suhaimi, Imam (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2020)
This research is a study of the scientific approach (with the 5M method) which is part ofthe implementation of the KKNI curriculum which will be applied in learning to writescientific papers. In connection with that, the research objective is to see the increase inthe ability of students in writing scientific papers by applying a scientific approach (the5M method). The method used is a quasi-experimental method, namely quasiexperimental with a one group pretest-postest design. The design only looks at thelearning outcomes of students before and after treatment with the scientific approach (5Mmethod). The sample that will be subject to treatment is 30 people from the entirepopulation. This was obtained from 30% of the 103 on year 2019 students who receivedthe Scientific Paper Writing Engineering course. While the test that will be used tomeasure the ability of students is the writing ability test. The test is made in the form of adescription. Learning outcomes were tested using the Liliefors normality test, testing datahomogeneity with the F homogeneity test, and testing hypotheses with the T-test Key Word: Scientific approach; Writing Skills